Research upon the trophic spectrum of a Triturus cristatus population in the Briheni area (County of Bihor, Romania) - CICORT–LUCACIU Alfred–Ştefan; COVACIU–MARCOV Severus–Daniel; CUPŞA Diana; PURGEA Ioana; SAS István (Scientific Annals of the Danube Delta Institute, 2005)
We studied the trophic spectrum of 131 exemplars of Triturus cristatus compared to the trophic offer available at the level of the habitat and depending on the sex of the individuals. The composition of the trophic spectrum varies during the whole year, as the feeding is influenced by the environmental factors and by the life cycle of different aquatic organisms that serve as prey for the tritons. There are differences of the trophic spectrum depending on the sex; the females eat immobile preys or less mobile preys than the males, as a consequence of the fact that the comb is missing. Triturus cristatus shows selectivity towards the accessibility, the dimension and the easy digestion of the prey. The combed tritons will consume the most spread taxon preys in the populated habitat, with the requirement that they have a certain size and are easy to capture.